THE ROLE OF OBSTETRIC NURSING IN THE EARLY IDENTIFICATION OF MATERNAL EMERGENCIES AND MORTALITY REDUCTION (International Seven Journal of Multidisciplinary, 2021)
Obstetric nursing plays a central role in reducing maternal mortality and morbidity, particularly through the early identification of emergencies. Obstetric nurses work on the front lines of care, being responsible for identifying risk signs, implementing swift interventions, and coordinating referrals to higher levels of care when needed. Early detection of complications like preeclampsia, severe hemorrhages, and infections can be decisive in saving lives. Well-structured protocols and health education for pregnant women are fundamental to ensuring that warning signs are promptly recognized and treated. The implementation of early warning systems (EWS), as highlighted in studies by Friedman et al. (2018) and Zuckerwise and Lipkind (2017), has shown promising results in reducing maternal complications. These systems allow for the early detection of clinical deterioration and timely intervention, which can significantly reduce mortality rates. The use of protocols, such as the Manchester Protocol, is an example of how structured triage can improve the quality of care in obstetric emergencies. Additionally, continuous training of healthcare teams and the enhancement of professional technical skills are essential to face the challenges of modern obstetrics. Training in critical care, such as point-of-care ultrasonography, and improving communication among multidisciplinary team members are key practices for effective response. Strengthening obstetric care through education and the implementation of innovative technologies leads to better maternal and fetal outcomes and reduces severe complications.